2018
DOI: 10.2174/1570162x15666171122155708
|View full text |Cite
|
Sign up to set email alerts
|

Integrase Strand Transfer Inhibitors and the Emergence of Immune Reconstitution Inflammatory Syndrome (IRIS)

Abstract: The use of INSTIs and especially DTG and EVG is associated with a higher probability for the development of IRIS in the background of late presentation and the presence of OIs. These data highlight the need for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 0 publications
1
31
1
1
Order By: Relevance
“…First-line INSTI ART regimens are associated with a higher incidence of immune reconstitution immunodeficiency syndrome (IRIS) (142, 143). IRIS, that can worsen existing opportunistic infections or unmask previously subclinical infections, very commonly M.tb , is associated with redistribution and restoration of functional memory T cells within the first months of ART (144).…”
Section: Specific Considerations/limitationsmentioning
confidence: 99%
“…First-line INSTI ART regimens are associated with a higher incidence of immune reconstitution immunodeficiency syndrome (IRIS) (142, 143). IRIS, that can worsen existing opportunistic infections or unmask previously subclinical infections, very commonly M.tb , is associated with redistribution and restoration of functional memory T cells within the first months of ART (144).…”
Section: Specific Considerations/limitationsmentioning
confidence: 99%
“…5 One factor that may have contributed to the high incidence of PML-IRIS was the high proportion of all patients who were treated with integrase strand transfer inhib-itors (INSTIs; 11 of 26, 42%), which have been previously shown to be associated with higher incidence of IRIS, felt to be related to the rapid decline in plasma HIV viral load. 19 INSTIs have been observed to have excellent CNS penetrance, 20 which has been shown to be associated with improved rates of HIV viral suppression within the CSF. 21 Unfortunately, viral suppression in the CSF has not correlated well with incident AIDS-defining neurological conditions, 22 so the adjustment of an ART regimen based on concern for PML or PML-IRIS is not supported at this time.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether integrase inhibitors increase the risk of paradoxical TB-IRIS as they result in a more rapid decline in HIV viral load has arisen with increasing use of integrase inhibitors in first-line ART regimens. Observational studies have reported an association with all-cause IRIS [ 22 , 23 ]. A recent meta-analysis addressing Dolutegravir use did not find an association with IRIS [ 24 ].…”
Section: Paradoxical Tuberculosis-associated Immune Reconstitution Inmentioning
confidence: 99%